Graphene in Supercapacitor Applications. Issue 5 (October 2015) - Yang, Wen; Ni, Mei; Ren, Xin; Tian, Yafen; Li, Ning; Su, Yuefeng; Zhang, Xiaoling
Abstract: The use of graphene-based materials for electrochemical double-layer capacitor (EDLCs) electrodes is reviewed. To establish a detailed understanding of the science and technology of graphene-based EDLCs, we summarize the key aspects of graphene-based materials, including specific surface area, pore size distribution, interlayer distance, heteroatom doping, surface functionalities, and conductivity. We also discuss the contribution of these physical–chemical properties to the capacitance and rate performance of graphene-based EDLCs. Although graphene is one of the most promising electrode materials for supercapacitors, many challenges still remain, particularly to establish a standardized measurement of capacitor performance, to reduce the price of graphene-based EDLC, to understand the mechanism of ion sorption on graphene, to study self-discharge mechanisms of graphene-based supercapacitors, to propose a new storage method for graphene-based EDLCs, etc. The full potential of graphene-based EDLCs as energy storage sources has not been fully developed, but as outlined in this review, the future looks very promising. Graphical abstract: